031 PCI in the elderly: what's the bleeding problem?. (22nd September 2015) - Lockie, T P E; Perera, D; Webb, I; De Silva, K; Pattinson, S; Redwood, S
Abstract : Background: With an ageing population the need for coronary revascularisation in the elderly is likely to continue to increase. There is a paucity of data detailing the outcome of these patients following percutaneous coronary intervention (PCI), particularly in the drug-eluting stent (DES) era with increasing use of multiple anti-thrombotic therapies. Methods: All patients undergoing PCI at St Thomas' between 2005 and 2009 were included and divided into groups according to their age (< or >80 years) and presentation (acute/elective). The primary endpoint was in-hospital MACCE, defined as the compositae of death, myocardial infarction, emergency revascularisation or cerebrovascular accident. The main secondary endpoint was major bleeding, defined by TIMI criteria. Data are presented as mean±SD. Results: Seven thousand five hundred seventy patients were included of which 514 were >80 years old. Elderly patients (83±2.68 years) undergoing elective PCI had a comparable MACCE (2.9% vs 2.8%, NS) to the younger group (63±9.4 years), but had a significantly higher rate of bleeding (3.3% vs 0.3%, p<0.0001). This was despite significantly lower glycoprotein IIb/IIIa inhibitor use in the >80 s group (15.8% vs 21.6%, p<0.0001). The incidence of MACCE following an acute presentation was higher in the elderly (7.5% vs 4.5%, p=0.02), with an increased need for circulatory support during PCI (6.6% vs 3.5%, p<0.0001) and a large increase in mortality (4.6% vs 1.9%, p<0.0001). DES were used more frequently in younger patients in an elective setting (average DES per patient of 0.9±1.1 vs 0.6±1.1, p<0.0001) but there was no difference in DES usage for acute PCI (0.6±1.1 vs 0.5±1.1, NS). Conclusion: PCI is safe mode of revascularisation in the elderly, although they have a poorer outcome than younger patients in the acute setting. There is an increased risk of major bleeding in the elderly, even after elective PCI, which will be especially pertinent with the use of newer and more potent anti-thrombotic drugs. >80 ACS (n=305) >80 elective (n=209) <80 ACS (n=3332) <80 elective (n=3724) Age 84±3.3 83±2.68 61±10.8 63±9.4 Male 167 (54.8%) 135 (64.6%) 2477 (74.3%) 2840 (76.2%) Shock 0 (0%) 0 (0%) 99 (3%) 0 (0%) Prev MI 137 (44.9%) 83 (39.7%) 1321 (39.6%) 1500 (40.2%) Prev CABG 39 (12.8%) 31 (14.8%) 242 (7.3%) 501 (13.4%) Prev PCI 50 (16.4%) 46 (22%) 508 (15.2%) 1071 (28.8%) DM 46 (15.1%) 42 (20.1%) 513 (15.3%) 709 (19%) Impaired LV 55 (18%) 30 (14.4%) 328 (9.8%) 324 (8.7%) Vessels attempted 1.4±0.7 1.3±0.5 1.3±0.6 1.3±0.5 Lesions attempted 1.6±0.8 1.5±0.8 1.4±0.7 1.5±0.7 No. stents 1.8±1.2 1.6±1.1 1.7±1.0 1.7±1.1 No. DES 0.5±1.1 0.6±1.1 0.6±1.1 0.9±1.1 GP inhib 75 (24.5%) 33 15.8%) 1572 (47.1%) 806 (21.6%) Circ support 20 (6.6%) 2 (0.9%) 116 (3.5%) 11 (0.3%) No. lesions successful 1.5±0.8 1.4±0.8 1.3±0.5 1.4±0.8 CRF 27 (8.9%) 16 (7.7%) 124 (3.7%) 109 (2.9%)